Effect of Exogenous Application of Jasmonic Acid on Date Palm Defense Reaction against Fusarium oxysporum f.sp. albedinis - Jaiti, F.; Dihazi, A.; El Hadrami, A.; El Hardami, A.; El Hassni, M.; El Hadrami, I. (Phytopathologia Mediterranea, 2004)
The effect of jasmonic acid in the date palm defence reaction against Fusarium oxysporum f. sp. albedinis was investigated taking into account changes in H2O2 and malonyldialdehyde (MDA) levels and peroxidase activity. Treatment of seedlings of two cultivars with jasmonic acid increased levels of H2O2 and enhanced lipid peroxidation as indicated by MDA accumulation and an increase in peroxidase activity. Similar changes occurred with date palm seedlings infected with Foa and showing necrotic hypersensitive-reaction like lesions. In general, both Foa and jasmonic acid increased H2O2 to a level 2 to 7 times that of the control, depending on the treatment and the time of analysis. Peroxidase activity was 2 to 3 times greater and MDA levels were increased 2 to 8 times. In contrast, seedlings presenting disease symptoms did not show any such reactions. It is suggested that oxidative burst (H2O2 generation) and its consequences (lipid peroxidation) and the change in peroxidase activity are used by date palm to resist Foa and that jasmonic acid is a signal for the expression of these defence reactions.